Type III Klippel-Feil syndrome with basilar invagination, syringomyelia, and spina bifida: a co-existence of rare congenital abnormalities - William, Munna; Fatima, Noor; Mehdi, Hassan; Shabbir, Ahmad; Nabeel, Muhammad; Anjum, Abdul Sattar (International Journal of Research in Medical Sciences, 2024)
Klippel-Feil syndrome (KFS) is a rare congenital skeletal anomaly characterized by the fusion of cervical vertebrae, often leading to a shortened neck, a low posterior hairline, and restricted neck movement. Despite its infrequency, KFS can present as a complex multisystem disorder including neurological and non-neurological defects, which rarely occur simultaneously. This report presents the case of a 20-year-old male diagnosed with KFS exhibiting basilar invagination, syringomyelia, and spina bifida, resulting in myelopathy and radiculopathy. Diagnostic imaging confirmed multiple vertebral fusions and associated neural tissue abnormalities. Surgical intervention, including spinal decompression, resulted in significant symptom relief. This case underscores the diverse clinical presentations and diagnostic challenges associated with KFS, necessitating a comprehensive approach with multiple imaging modalities for accurate diagnosis and tailored management. Prompt identification and intervention are crucial, particularly in cases of symptomatic anomalies, to prevent neurological decline and optimize patient outcomes. The presence of symptomatic basilar invagination underscores the importance of timely surgical intervention to prevent future neurological complications